2005
DOI: 10.1200/jco.2005.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Experience With the Novel Proteasome Inhibitor Bortezomib in Patients With Indolent Non-Hodgkin's Lymphoma and Mantle Cell Lymphoma

Abstract: These data suggest that bortezomib was well tolerated and has significant single-agent activity in patients with certain subtypes of NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
375
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(388 citation statements)
references
References 29 publications
9
375
1
3
Order By: Relevance
“…Thus, BIM could be involved in the mechanism of action of bortezomib, which inhibits proteasome and is used in CLL treatment. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, BIM could be involved in the mechanism of action of bortezomib, which inhibits proteasome and is used in CLL treatment. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibitors of the proteasome have recently received much attention in the light of their potent antitumor activity [1,2]. In this setting, bortezomib (Velcade) was demonstrated to be effective in the treatment of multiple myeloma and non-Hodgkin's lymphoma, when taken alone or in combination with traditional anticancer drugs [3][4][5][6][7]. Similarly, preliminary studies indicated that proteasome inhibitors induce clinical responses in patients with acute leukemia, prostate cancer, renal cell carcinoma, neuroendocrine tumors, and in children solid tumors [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy patients' pretreatment and/or pre-existing diseaserelated immunodepression hamper the evaluation of the immune effects of proteasome inhibitors in humans. However, lymphopenia was reported in some of the clinical studies carried out to date [4, 6,7] and may be related to inhibition of intracellular signaling pathways and/or to a direct pro-apoptotic effect of bortezomib in normal and malignant lymphocytes [17, 20, 22, 26, and A.N., unpublished observations]. On the other hand, proteasome inhibitors were shown to delay neutrophil apoptosis by favoring accumulation of the anti-apoptotic factor Mcl-1 [17,27].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Single-agent bortezomib demonstrated clinical activity in several other hematologic malignancies 5 with especially encouraging results in relapsed or refractory mantle cell lymphoma (MCL). [6][7][8] Objective response is achieved in 29-45% of MCL patients; however, complete remission rates are low and median duration of response short. These limitations may be overcome by combining bortezomib with conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%